Teknik Selling Skills untuk Meningkatkan Kompetensi Pemasar di PT Pos Logistik Indonesia - Suarsa, Senny Handayani (J-Dinamika : Jurnal Pengabdian Masyarakat, 2023)
PT Pos Logistik Indonesia (Poslog) is a subsidiary of PT Pos Indonesia (Persero) engaged in logistics services in Indonesia. This business opportunity in Indonesia is quite promising, with significant growth from year to year. Therefore, its human resources must be properly maintained, including professional marketers, who become the company's spearhead and valuable assets. The problem that often arises is their need for more knowledge about sales techniques (lack of competence in marketing). On the other hand, their knowledge and competence in the field of logistics are capable, and the high employee turnover in this section results in poor knowledge transfer. Equally, one way to improve employees' knowledge, skills, and abilities and skills, especially marketers, is through selling skills training. This training is expected to increase expertise, especially knowledge about selling skills for marketers in Poslog. This activity is done by evaluating understanding at the beginning, delivering material through video conference, discussion, question and answer, and evaluation at the end. The result of this activity showed an increase in the selling skills of employees before and after the training, which was seen from the skills of prospecting, approaching, probing, presenting, handling objections, and closing the sales.